Prolonged duration of type 2 diabetes is associated with increased thrombin generation, prothrombotic fibrin clot phenotype and impaired fibrinolysis - Konieczynska, Malgorzata; Fil, Korneliusz; Bazanek, Marta; Undas, Anetta (Thrombosis and Haemostasis, 2014)
It has been shown that type 2 diabetes (DM) is associated with enhanced thrombin generation and formation of denser fibrin clots of reduced lysability. We sought to investigate the impact of diabetes duration versus glycaemia control on fibrin clot phenotype and its determinants in type 2 diabetic patients. In 156 consecutive Caucasian patients with type 2 diabetes we investigated ex vivo thrombin generation, fibrinolytic proteins, along with plasma fibrin clot permeation (Ks), compaction, turbidity, and efficiency of tissue plasminogen activator (t-PA)-mediated fibrinolysis. Patients with longer diabetes duration (>5 years, median; n=68) had higher peak thrombin generation (+16.3%, p<0.001), plasminogen activator inhibitor-1 (PAI-1) antigen (+14.8%, p=0.001), t-PA antigen (+13.9%, p=0.002) compared with those with duration ≤5 years (n=88). No such differences were observed between patients with inadequate glycaemic control, defined as glycated haemoglobin (HbA1C) >6.5% (48 mmol/mol) (n=77), versus those with HbA1C ≤6.5% (n=79). Fibrinogen, thrombin-activatable fibrinolysis inhibitor antigen, plasminogen and soluble thrombomodulin were unaffected by disease duration or glycaemia control. Lower clot permeability, longer clot lysis, and higher maximum D-dimer levels released from clots (all p<0.05 after adjustment for fibrinogen, age, body mass index, insulin, acetylsalicylic acid treatment, and HbA1c or diabetes duration) were also observed in patients with diabetes duration >5 years and those with HbA1C >6.5%. We conclude that prolonged duration of type 2 diabetes is associated with increased thrombin formation, hypofibrinolysis, and prothrombotic fibrin clot phenotype. The impact of disease duration on coagulation is different and stronger than that observed during inadequate glycaemia control.
Keywords: Diabetes; glycaemic control; fibrin clot; fibrinolysis; thrombin